Relationship Between Consumer Awareness and Purchase Intention for Environmentally Friendly Products among Gen-Z in Penang - Yeap, Shan Wen; Hashim, Fazian (Research in Management of Technology and Business, 2025)
This research investigates the relationship between consumer awareness and intention to purchase environmentally friendly products, which has increasingly grown among Generation Z. This scenario emphasizes the level of consumer awareness, including four dimensions such as environmental knowledge, environmental concern, subjective norms, and perceived behavioural control to influence the consumer’s purchase intention. This is because there is still a large research gap in comprehending Gen-Z consumers' awareness level and purchasing intention for green products in Penang, Malaysia. While there is evidence of consumers moving towards sustainable consumption globally, studies focusing on the Penang region are scarce. This deficiency hinders the formulation of specific marketing approaches and policies, which are crucial in enhancing green purchasing behaviour among this group. Thus, the research aims to identify the level of consumer awareness and the level of purchase intention towards environmentally friendly products and investigate the relationship between consumer awareness and purchase intention. This study adopted a quantitative research approach, data were collected from 380 respondents via questionnaires to collect data among Gen-Z in Penang. The data was analysed using the Statistical Package for Social Science (SPSS), which employs descriptive and data analysis. The outcome indicated that all four dimensions of consumer awareness and purchase intention had a significant and positive correlation among Gen-Z in Penang. The research findings conclude environmental knowledge had the strongest relationship with purchase intention among the three dimensions. This study provide valuable insights to help increase awareness and intention to purchase sustainable products among Generation Z to decrease environmental impact.